2004
DOI: 10.2460/ajvr.2004.65.1216
|View full text |Cite
|
Sign up to set email alerts
|

Role of the tendons of the biceps brachii and infraspinatus muscles and the medial glenohumeral ligament in the maintenance of passive shoulder joint stability in dogs

Abstract: The BBT contributes to passive shoulder joint stability in dogs, particularly in the neutral and flexed positions. It also provides medial stability during shoulder joint extension. Complete luxation of the joint occurs when the MGHL is transected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 23 publications
(32 reference statements)
1
59
1
2
Order By: Relevance
“…The cuff muscles include the infraspinatus, supraspinatus, subscapularis, and teres minor muscles. The medial and lateral glenohumeral ligaments, the joint capsule, and the articular surfaces act as static stabilizers . To maintain shoulder stability, the integrity of the medial glenohumeral ligament (MGHL) and the subscapularis tendon is essential .…”
Section: Introductionmentioning
confidence: 99%
“…The cuff muscles include the infraspinatus, supraspinatus, subscapularis, and teres minor muscles. The medial and lateral glenohumeral ligaments, the joint capsule, and the articular surfaces act as static stabilizers . To maintain shoulder stability, the integrity of the medial glenohumeral ligament (MGHL) and the subscapularis tendon is essential .…”
Section: Introductionmentioning
confidence: 99%
“…Pathology of the active or passive stabilizing structures can cause this instability, which can also result in lameness . The active stabilizers of the glenohumeral joint are the supraspinatus, infraspinatus , subscapularis, biceps, and teres minor muscles; the passive stabilizer is the capsular complex, including the synovial membrane and the glenohumeral ligaments . Determining the exact cause of shoulder instability is often difficult and may require both intra‐ and extra‐articular assessments.…”
Section: Introductionmentioning
confidence: 99%
“…The most common cause of forelimb lameness in dogs has been reported to be associated with instability of the glenohumeral joint 1 . Shoulder instability has been defined as an abnormal translation of the humeral head within the glenoid fossa resulting in discomfort and dysfunction of the shoulder joint, which is the result of incompetence or disruption of the shoulder joint stabilizing mechanisms 2 . The abnormal translation that is characteristic of shoulder instability enables further classification of the disorder based on structure(s) involved.…”
Section: Introductionmentioning
confidence: 99%
“…The stabilizers of the joint limit excessive motion, and can be subdivided into passive, or static, stabilizers (joint capsule, joint congruity, joint fluid volume, and medial and lateral glenohumeral ligaments) and active, or dynamic, stabilizers (biceps, subscapularis, supraspinatus, infraspinatus, and teres minor) 1–4,10 . The significance of pathology of each stabilizer with respect to clinical function has not been determined, but ex vivo analyses have shown that disruption of the medial glenohumeral ligament consistently resulted in medial shoulder luxation, increased abduction angles, and increased external rotation 2,6 . From retrospective studies, the medial glenohumeral ligament is the most commonly affected stabilizer in the shoulder leading to a diagnosis of medial shoulder instability 1–5,7,8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation